Proceedings of the 1st International Conference on Science, Health, Economics, Education and Technology (ICoSHEET 2019) 2020
DOI: 10.2991/ahsr.k.200723.044
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Health Behavior and Quality of Life of the Elderly

Abstract: The increasing number of elderly will require serious treatment for the elderly naturally decline, physical, biological, and mental. People, especially the elderly in PasirMulya have bad habits in terms of preparing food, eating food, such as frequently eating fast food. To analyze the relationship between health behavior and quality of life of the elderly. Quantitative approach to the cross-sectional design. Population of 92 elderly people with samples taken using total sampling technique. Statistically using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…Nevertheless, the quality of life and healthy lifestyle must continuously improve. This finding is also in line with a study conducted by Lestari & Zakiah (2020) which concluded that the health behavior of the elderly affects their quality of life, in which poor health behavior may worsen their quality of life. They added that healthy behavior, especially in the elderly, must be comprehensive and continue to be improved and taught.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the quality of life and healthy lifestyle must continuously improve. This finding is also in line with a study conducted by Lestari & Zakiah (2020) which concluded that the health behavior of the elderly affects their quality of life, in which poor health behavior may worsen their quality of life. They added that healthy behavior, especially in the elderly, must be comprehensive and continue to be improved and taught.…”
Section: Discussionsupporting
confidence: 92%